The Influence of Educational Determinants on Children's Health : A Scoping Review of Reviews - Fillol, Amandine; Wallerich, Louise; Larose, Marie-Pier; Ferron, Christine; Rivadeneyra-Sicilia, Ana; Vandentorren, Stéphanie; Brandler-Weinreb, Jessica; Cambon, Linda (Frontiers Media S.A., 2025)
Objectives: Education is one of the most important social determinants shaping the development and wellbeing of children. The purpose of this review of reviews is to inform policymakers, practitioners and public health stakeholder involved in developing child-friendly policies outside of the healthcare system.
Methods: We carried out a scoping review of reviews. It included 32 reviews.
Results: We identified four main categories of educational determinants in relation to children's health: 1) the organization and structure of educational activities, 2) the interpersonal relations in the educational facilities and structures, 3) the spatial environment of educational facilities and structures, 4) social inequalities in the educational facilities and structures. This last category highlighted the capacity of education system to act on inequalities derived from the way social structures are organized.
Conclusion: We suggest a conceptual framework for action which distinguishes structural determinant (gender, race, social class, etc.) and structuring determinant (public policy, systems of governance, organization of cultures/values consideration). Finally, we discuss on how these social structures and structuring determinants influence the intermediary educational determinants collated in the review.